Penerapan Konseling Individu Menggunakan Teknik Relaksasi untuk Mengatasi Insomnia pada Remaja - Deni Anggik Ptrian; Neni Noviza (Journal of Society Counseling, 2025)
Insomnia is a common sleep disorder among adolescents, often triggered by psychological pressure, parent–child conflict, and unhealthy lifestyle habits. This study aims to describe the experience of insomnia among adolescents in Suka Mulya Village and to analyze the implementation of individual counseling using relaxation techniques in addressing it. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation involving four adolescent subjects. Data were analyzed through data reduction, data display, and conclusion drawing. The results indicate that insomnia among the four subjects was influenced by psychological factors (pressure and conflict with parents), lifestyle factors (caffeine consumption and late-night habits), and environmental factors (noise disturbance around their residence). The implementation of individual counseling with relaxation techniques produced positive outcomes, reflected in the counselees' enthusiasm during the counseling process and improvements in sleep patterns, overall health condition, and reduced difficulty initiating sleep at night. These findings are consistent with previous studies demonstrating the effectiveness of cognitive-behavioral approaches and relaxation techniques in managing insomnia among adolescent populations.